Parvovirus В19 infection: lecture - T. M. Chernova; V. N. Timchenko; E. B. Pavlova; E. V. Baracina; M. D. Subbotina (Детские инфекции (Москва), 2022)
Parvovirus B19 infection is best known as erythema infectiosum. However, infection with parvovirus B19 can lead to damage to various organs and systems, the development of severe complications up to death. The infection is most dangerous for people with immunodeficiency and hematological diseases. Serious consequences are possible with intrauterine infection of the fetus. Knowledge about the characteristics of the pathogen, the pathogenesis of the disease, the variety of clinical manifestations will allow the doctor to avoid diagnostic errors and provide the patient with timely medical care.